UV-C light as an alternative for disinfecting orthodontic pliers - Rossi Lucas , Leidiani; Navarro, Ricardo Scarparo; de Oliveira, Andreia; Sayuri Suzuki , Selly; Silva Garcez , Aguinaldo (Brazilian Dental Science, 2023)
Objective: Orthodontists use orthodontic pliers continuously, and these tools have a strong potential for nosocomial infections. This study aimed to compare the efficiency of three methods for disinfecting orthodontic pliers. Material and Methods: The active tips of 26 orthodontic pliers (distal end cutters and Weingart pliers) were contaminated with S. aureus, E. coli, and C. albicans microorganisms, viruses, and spores. The microbial control methods were 70% alcohol disinfection, glass bead sterilization (250 °C dry heat), and ultraviolet light irradiation (250 nm UV-C) for 30 and 60 seconds. The number of colony-forming units (CFU) and plaque-forming units (PFU) was quantified and compared for each microorganism after incubation in culture plates. Results: All tips of the pliers in the groups that received ultraviolet light or were subjected to glass bead sterilization showed a significantly lower number of spores, bacteria, and fungi than their respective control samples (p<0.001). Physical disinfection with UV-C light may represent a reliable alternative compared to other chemical and physical methods due to the increase in microorganisms resistant to chemical products and the emission of harmful by-products after chemical treatment. Conclusion: The tested microbial control methods were effective in the disinfection of orthodontic pliers, making ultraviolet-C light a promising alternative to eliminate microorganisms from pliers. KEYWORDS Biosafety; Contamination; Disinfection; Microorganisms; Ultraviolet light.